Performance Evaluation of Centralized In-Network Caching and Content Visibility in Information Centric Network over SDN/OpenFlow - Chanthan Hel; Chaiyachet Saivichit (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Performance is the main issue that we must consider as the key point in order to design Information Centric Network architecture (ICN). Cooperative in-network caching and ability of network’s nodes to see the contents in network will improve performance of ICN. In centralized network, the controller plays very important role in order to enable ICN nodes to do cooperative caching. Also, it has ability to see contents partially or globally according to our configuration. This paper aims to observe and compare the performance of ICN when we apply different levels of cooperative in-network caching and content visibility based on centralized control by using SDN/OpenFlow concept. We will evaluate performance of ICN by using three mechanisms; firstly, non-cooperative in-network caching with individual visibility; secondly, path cooperative in-network caching with path content visibility; and finally, global cooperative in-network caching with global content visibility. Our emulation result shows that global cooperative in-network caching with global content visibility mechanism gives better performance for ICN in terms of average number of hops to reach the content and number of requests hit server.